Kualitas Lingkungan Keluarga di Kawasan Candi Batujaya - Elmanora Elmanora; Mulyati Mulyati; Kenty Martiastuti (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
The quality of the family environment is one of the important foundations in building a good society. This study aims to analyze the quality of the family environment that lives in the Batujaya Temple area, Karawang Regency, West Java Province, Indonesia. Data has been collected from April to May 2019. This study was involved 100 families that have been selected using simple random techniques. Data consist of family characteristics and the quality of the family environment. The quality of the family environment was measured using the "Family Environment Scale" instrument compiled by Moos and Moos (2002). Family Environment Scale consists of relationship dimensions (cohesion, expression, and conflict), personal growth dimensions (independence, achievement orientation, intellectual-cultural orientation, active-recreation orientation, and moral-religion orientation), and also system maintenance dimension (control and organization). The instrument consists of 40 item statements. The quality of the family environment is categorized into three categories: low (index<60.0), moderate (index 60.0-80.0), and high (index > 80.0). Furthermore, the data were analyzed using descriptive analysis. The results showed that most of the quality of the family environment in relationship dimensions included in the high category, but included in the medium and low categories for personal growth dimensions and system maintenance dimensions. These results indicate that there needs to be an effort that can help families to carry out their functions in achieving a good quality of family environment.Keywords - Batujaya Temple, Cultural Heritage, Family Function, Family Environment.